2017
DOI: 10.1007/s10967-017-5644-9
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring evaluation of some toxic and trace elements in the sea urchin Lytechinus variegatus (Lamarck, 1816) in a marine environment: northern coast of São Paulo (Brazil)

Abstract: This study aimed to evaluate the sea urchin Lytechinus variegatus as an environmental biomonitor and contribute to the knowledge of its nutritional aspects for two regions of the northern coast of the São Paulo State, Brazil. Mass fractions were determined by instrumental neutron activation analysis. Concentrations of Ca, Cs, Cr, Fe, Rb, Sc, and Zn were higher at Praia Grande (contaminated area), while As, Br, and Se higher at Praia Preta (control). An exploratory principal component analysis indicated that Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
2
0
3
Order By: Relevance
“…Some studies have investigated spatial variations in element concentrations near sources of anthropogenic pollution in P. lividus and other sea urchin species such as Strongylocentrotus droebachiensis and Lytechinus variegatus . In these studies, high concentrations of several elements were observed near polluting sources, and these species were proposed as biomonitors for several elements, like for instance Fe, Cu, Zn, Cd, and Pb (Scanu et al 2015 ; Alves et al 2018 ; Rouane-Hacene et al 2018 ; Ternengo et al 2018 ; Søndergaard et al 2019 ; Ouchene et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have investigated spatial variations in element concentrations near sources of anthropogenic pollution in P. lividus and other sea urchin species such as Strongylocentrotus droebachiensis and Lytechinus variegatus . In these studies, high concentrations of several elements were observed near polluting sources, and these species were proposed as biomonitors for several elements, like for instance Fe, Cu, Zn, Cd, and Pb (Scanu et al 2015 ; Alves et al 2018 ; Rouane-Hacene et al 2018 ; Ternengo et al 2018 ; Søndergaard et al 2019 ; Ouchene et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Entre os organismos utilizados mundialmente, os bivalves têm se destacado em diversos estudos (YUSOF et al, 2004;GALVÃO et al, 2009;. Entretanto, vários estudos incluem outros organismos como biomonitores do ambiente marinho, como algas (CONTI e CECCHETTI, 2003;ZBIKOWSKI et al, 2007;MAJER et al, 2014), e ouriços (MAJER et al, 2014;ALVES et al, 2017). Ressalta-se aqui que ouriços são mais utilizados em ensaios ecotoxicológicos (PINSINO e MATRANGA, 2015;PAIVA et al, 2012.…”
Section: Biomonitoramento E Diagnóstico Ambientalunclassified
“…study performed with Perna perna mussels [19]. Moreover, Br in these samples has same magnitude of concentration as in L. variegatus urchin species (ALVES, 2017). Although the concentrations are statistically different, nothing can be said about anthropic sources for this element without sedimentary data from the regions.…”
mentioning
confidence: 90%
See 2 more Smart Citations